Development of Cu-Al-Ni alloy for dental post and core application - Apiwat Rittapai (Mahidol University. Mahidol University Library and Knowledge Center, 2023)
Generally, the technique used for replacement of the tooth is "posts and cores". Noble and semi-precious dental alloys have numerous excellent properties, but they are expensive and unaffordable for lots of patients. The copper-aluminum-nickel alloy is a reasonably priced alternative, and theoretically is perceived as corrosion resistant. Therefore, this situation could potentially be a prototype to develop a base-metal alloy for dental post and core application, and generate dentistry that is more affordable to patients. Sixteen groups of experiment alloys, with varying proportions 0, 3, 6, 9 wt % Al and 0, 2, 4, 6 wt % Ni, were prepared and their properties were evaluated. As generated by the biocompatibility characteristic, the 6 wt % Ni series was inappropriate for use for this purpose, due to its high toxicity. Also, the 12 wt % Al series was not suitable due to its high brittleness and low castability. Additionally, the 0 wt % Ni series revealed extremely low strength and elongation, and the 6 wt % Al series exhibited only a small amount of modulus to withstand mastication in the mouth. As a result, the 9 wt % Al with the combination of 2 wt % Ni and 4 wt % Ni series not only produced appropriate modulus of elasticity (63.9±5.1 to 139.1±14.2 GPa), predictable on the point of dental gold alloy, and presented higher corrosion resistance than the others, but also had a value of 0.2 % proof strength (180.4±5.8 to 198.2±3.4 MPa), which complied with the ISO standard of at least 180 MPa. In conclusion, the 9 wt % Al in the combination of 2 wt % Ni and 4 wt % Ni series has the potential to present for dental post and core application, and is capable of being used for further development as good quality post-and-core material.